Analysis of the State and Development of Vehicles Working in the Quarry - Kamoliddin Juraboevich Rustamov; Ilhom Ikromjanovich Usmonov (International Journal on Orange Technologies, 2022)
This article provides information about cars operating in a quarry, which is the main traffic flow of industrial vehicles. An analysis is also given of opinions on the serious development of road transport, due to its criteria and advantages, in comparison with rail transport and conveyor modes of transport.